Nanotechnology-Based Drug Delivery Systems for Targeted Cancer Therapy - Dans, Maricar Leonila; Toquero, Concepcion Mae; Alampah, Liane Regulacio (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2025)
Nanotechnology has emerged as a transformative approach in cancer therapy by enabling precise, targeted, and controlled delivery of therapeutic agents. This systematic review aims to evaluate the clinical advances of nanotechnology-based drug delivery systems in oncology, focusing on their efficacy, safety, and translational potential. Using PRISMA guidelines, relevant studies from 2015 to 2025 were analyzed, including randomized clinical trials, cohort studies, and systematic reviews. Findings demonstrate that nanoparticle formulations—such as liposomes, polymeric nanoparticles, dendrimers, and gold nanoparticles—significantly enhance bioavailability and tumor-specific accumulation while minimizing off-target toxicity. For example, liposomal doxorubicin and albumin-bound paclitaxel have shown improved survival outcomes and reduced cardiotoxicity compared to conventional chemotherapy. Recent advances in stimuli-responsive and ligand-functionalized nanoparticles have further increased precision in drug release, resulting in better therapeutic indices in breast, lung, and prostate cancers. Despite these achievements, challenges remain in large-scale production, cost efficiency, and long-term biocompatibility. Regulatory hurdles and variability in patient-specific responses also limit broader adoption in clinical practice. Overall, nanotechnology-based drug delivery systems represent a paradigm shift in targeted cancer therapy, offering enhanced treatment precision, improved patient quality of life, and potential integration with immunotherapy and gene therapy approaches. Future clinical research should prioritize personalized nanomedicine, long-term safety monitoring, and scalable production to maximize clinical translation.